Gambaran Perilaku Non-Suicidal Self-Injury (NSSI) Pada Siswa SMAN 1 Bogor - Afra Hasna; Thrisia Febrianti Febrianti; Dita Juwita Zuraida (Guidance : Jurnal Bimbingan dan Konseling, 2023)
Late adolescence to early adulthood is called a problematic period. Self-injury is an attempt to avoid distressing thoughts, feelings, or internal experiences by intentionally injuring oneself without suicidal intent. The purpose of this study was to describe the behavior of NSSI among students in SMAN 1 Bogor. The research method used is qualitative research with in-depth interviews and observational models. The research subjects were two people using a purposive sampling technique. The data collection technique used was the SelfHarm Behavior Questionnaire (SHBQ) and the results of an IPA (interpretative phenomenological analysis) analysis. The results of research on NSSI behavior were triggered by negative treatment received, such as bullying and a lack of acceptance and support from parents, so there was a feeling of pressure and not being accepted. NSSI is carried out to reduce tension and divert negative feelings until there are attempts to end one's life with a suicide attempt. The weakness of this study is that it only provides an overview of NSSI behavior and doesn’t provides interventions for resolution and prevention of NSSI behavior